Childhood trauma and violent behavior in adolescents are differentially related to cognitive-emotional deficits - Stephen Katembu; Anoushiravan Zahedi; Anoushiravan Zahedi; Anoushiravan Zahedi; Werner Sommer; Werner Sommer (Frontiers Media S.A., 2023)
IntroductionConverging neurobiological and epidemiological evidence indicates that exposure to traumatic events in the early stages of development, that is, adverse childhood experiences (ACEs), negatively affects the likelihood of being involved in violent behavior later in life. These problems are hypothesized to be mediated by the disruption of executive functions, in particular, the ability to inhibit inappropriate actions. Here we aimed to distinguish the contribution of inhibition in non-emotional and emotional situations (i.e., emotion regulation) and assessed the modulating influence of stress, testing Nairobi county high school students in a two-experiment study.MethodsIn Experiment 1, neutral and emotional inhibition, working memory, and fluid intelligence were measured alongside questionnaires about ACE and violent behavior. Experiment 2 replicated these relations in an independent sample and assessed whether they would be aggravated after acute experimentally induced stress.ResultsExperiment 1 results showed that ACE was positively related to both non-emotional and emotional inhibition; in contrast, violent behavior was only associated with deficient emotional inhibition. Experiment 2 findings showed that stress did not significantly affect the relation of ACE to non-emotional inhibition and emotion regulation; however, it increased deficits of violent participants in their ability to down-regulate emotions.DiscussionTogether, results suggest that deficits in emotion regulation, especially under stressful conditions, are more critical than impairments in non-emotional inhibition in predicting violent behavior in victims of childhood trauma. These findings open perspectives toward more targeted research and interventions.